Attention Deficit and EEG Analysis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
Computerized power spectral analysis (PSA), permitting topographic representation and statistical analysis of EEG, of 25 right-handed males, 9-12 years of age with attention deficit hyperactivity disorder was used in studies from the Departments of Psychology, Pediatrics (Neurology) and Computing Center, University of Tennessee and East Tennessee Children's Hospital, Knoxville, TN.